Analysis of the impacts of the COVID-19 pandemic on people living with HIV/AIDS in a reference unit in Maceió – Alagoas - Silva, Dalton Bernardino Santos; Panjwani, Camila Maria Beder Ribeiro Girish; Ferreira, Juliana Maria Bulhões; Torres, Vitoria Cruz; Barreto, Priscilla Cordeiro; Santos, Jordanna Daynne Vieira dos; Silva, Paloma Pereira da; Silva, Maria Eduarda Lopes da (Seven Editora, 2023)
Introduction: Due to social distancing due to the COVID-19 pandemic, the habit of sexual practices may have been affected, which impacts the alteration of the exposure of individuals to HIV infection. However, data on sexual behavior among Alagoas are still unknown. Objective: To analyze the impacts of the COVID-19 Pandemic on people living with HIV/AIDS in a Reference Unit of Maceió-Alagoas. Methods: This is an exploratory and descriptive study with a quantitative approach of the documentary type. The sample comprises 183 questionnaires applied from August 2021 to March 2022 to individuals undergoing HIV testing at the Specialized Care Service (SAE) of PAM Salgadinho, in addition to the analysis and comparison with the specialized literature. Results: The major cause of the search for the rapid test resulted from unprotected sexual intercourse, representing 36.00% of the cases. When asked if the pandemic affected the usual number of sexual partners, 78 (42.60%) answered yes, and 61 (78.21%) of them claimed that there was a decrease. Asked about the practice of sexual activity, it was observed that 34.43% of the interviewees said they had interrupted it. However, for 52.46% of those who remained sexually active, there was an increase in the number of unprotected sexual relations. Conclusion: It can be observed that, with the measures of social isolation, there was a reduction in the number of sexual contacts with different people among the interviewees. In addition, a significant number of individuals reported having ceased their sexual activities during the period. This may have had a positive impact on reducing HIV exposure. DOI:https://doi.org/10.56238/globalhealthprespesc-002